2014
DOI: 10.1371/journal.pone.0115840
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Novel Fusion Protein of a Mutated Granulocyte Colony-Stimulating Factor and Human Serum Albumin in Pichia pastoris

Abstract: The purpose of the present work was to develop a novel, long-acting and potent human serum albumin/granulocyte colony stimulating factor (HSA/G-CSF) therapeutic fusion protein. The novel fusion protein, called HMG, was constructed by genetically fusing mutated human derived G-CSF (mG-CSF) to the C-terminal of HSA and then prepared in Pichia pastoris. The molecular mass of HMG was about 85 kDa and the isoelectric point was 5.3. Circular dichroism spectroscopy suggested that mG-CSF retained nearly all of its nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…P. pastoris can effectively secrete large amounts of recombinant HSA and HSA fusion proteins 39 41 . We constructed a strain expressing two fusion proteins (pJC172): (i) HSA-hGH, consisting of an alpha-mating factor secretion signal, HSA, a tobacco etch virus (TEV) protease cleavage site, and hGH; and (ii) Golgi-TEV, consisting of a Golgi apparatus localization signal (the membrane-binding domain of alpha-1,2-mannosyltransferase) and TEV protease 26 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…P. pastoris can effectively secrete large amounts of recombinant HSA and HSA fusion proteins 39 41 . We constructed a strain expressing two fusion proteins (pJC172): (i) HSA-hGH, consisting of an alpha-mating factor secretion signal, HSA, a tobacco etch virus (TEV) protease cleavage site, and hGH; and (ii) Golgi-TEV, consisting of a Golgi apparatus localization signal (the membrane-binding domain of alpha-1,2-mannosyltransferase) and TEV protease 26 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that single injections of PEG-rhG-CSF were at least as potent as multiple injections of rhG-CSF in treating neutropenia [42]. Fusion of rhG-CSF to an Fc receptor [43] or serum albumin [44,45] was effective in increasing half-life of rhG-CSF and thus mobilization efficiency. In all of these studies, plasma levels of rhG-CSF were considered to be a marker for effectiveness of the modification.…”
Section: Discussionmentioning
confidence: 99%
“…However, accurate glycosylation cannot be ensured for recombinant proteins expressed in yeasts and this will require extensive structural studies for confirmation. The aberrant glycosylation pattern often causes antigenicity of recombinant proteins which may induce production of neutralizing antibodies in the subject and unpredictable pharmacokinetic manifestations . Highly mannosylated proteins are for example linked to mannose binding endocytic receptors in antigen‐presenting cells .…”
Section: Discussionmentioning
confidence: 99%